Let farmers judge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Let farmers judge: experiences in assessing the sustainability of agriculture edited by Wim Hiemstra, Coen Reijntjes and Erik van der Werf 1992 208pp ISBN 1 85339 1492 Pbk Price UKL12.95 IT Publications 103-105 Southampton Row London WC1B 4HH, U